Phase II Study of Preoperative Capecitabine and Oxaliplatin-based Intensified Chemoradiotherapy With or Without Induction Chemotherapy in Patients With Locally Advanced Rectal Cancer and Synchronous Liver-limited Resectable Metastases. (December 2016) - Cho, Hyungwoo; Kim, Jeong Eun; Kim, Kyu-pyo; Yu, Chang Sik; Kim, Jin Cheon; Kim, Jong Hoon; Lee, Myung Ah; Jang, Hong Seok; Oh, Seong Taek; Kim, Sun Young; Oh, Jae Hwan; Kim, Dae Yong; et al.
Abstract : Objectives: Controversy surrounds the management of patients with locally advanced rectal cancer with synchronous resectable liver metastases (LMs). This study was designed to improve both systemic and local control in these patients. Methods: Patients with locally advanced rectal cancer (cT3-4N0 or cTanyN1-2) and synchronous resectable liver-limited metastases (cM1a) were randomly assigned to receive either preoperative treatments of induction CapeOx, followed by chemoradiotherapy with CapeOx (CapeOx-RT) (arm A) or CapeOx-RT alone (arm B). Induction CapeOx consisted of oxaliplatin 130 mg/m 2 on day 1 and capecitabine 1000 mg/m 2 twice daily on days 1 to 14, every 3 weeks for 2 cycles; CapeOx-RT consisted of radiotherapy with 45 Gy/25 daily fractions±5.4 Gy/3 fractions, oxaliplatin 50 mg/m 2 weekly for 5 weeks, and capecitabine 825 mg/m 2 twice daily on days 1 to 38. Total mesorectal excision and simultaneous liver metastasectomy were planned within 6 weeks after completion of preoperative treatments. The primary endpoint was R0 resection rate of both the primary tumor and LMs. Results: Thirty-eight patients were randomly assigned to the present study, 18 to arm A and 20 to arm B. The overall R0 resection rate for both the primary tumor and LMs was 77.8% in arm A and 70.0% in arm B ( P =0.72). The median progression-free survival was 14.2 versus 15.1 months ( P =0.422) and the 3-year overall survival rate was 75.0% versus 88.8% ( P =0.29), respectively. Conclusions: Both treatment strategies showed considerable R0 resection rates; however, further study will be warranted to apply these intensified strategies in clinical practice. Abstract : Supplemental Digital Content is available in the text.